Regulating On-demand Work in China: Just Getting Started?. (17th May 2021) - Lin, Ou
Abstract: In China, a significant and rising number of workers are engaged in on-demand work. The legal status of on-demand workers has been widely debated, and it seems that the vast majority are not protected by labour law, since the law accords rights only to those workers with 'labour relationships'. While there is widespread consensus in China that on-demand workers need more protection, steps taken in that direction to date have been small indeed. This paper seeks to explain the current legal situation of Chinese on-demand workers by outlining the responses to the spread of on-demand work of the judicial and arbitration system, national government, trade unions and workers themselves. Addressing the question why on-demand workers have not yet been accorded labour protections, it points in particular to the national government's concern to maintain high levels of employment and ensure economic growth.